Appraisal of Transition Challenges and Adjustment of First-Year Students at a Nigerian University - Fabeku, Oluwatimilehin Emmanuel; Fasanmi, Success Ayodeji (Educational Challenges, 2024)
Advancement in educational pursuit seems to be an ideal dream for the majority of students preparing to leave secondary school to enter university. Students at this stage have conceptualized courses and professions they would like to follow, the types and names of universities they would like to attend, and are mostly overwhelmed by the euphoria of leaving secondary school for university without the knowledge of the demands, the challenges and the expected behavior awaiting them in their envisioned dream of an institute of higher learning. Purpose: This paper appraised the transition challenges and adjustment strategies of first-year students in Obafemi Awolowo University, Ile-Ife, Nigeria. Methodology: A descriptive survey research design was employed. A simple random sampling technique was used in selecting five of the eight departments in the Faculty of Education. A convenience sampling technique was used in selecting 200 participants in the departments selected for the study. A questionnaire titled ‘First Year Students Transition Challenges and Adjustment Questionnaire’ (FYSTCAQ) made up of four sections was used to obtain data from the sample. Results: The findings showed that first-year students experience transition challenges among which are cultural, social and economic. Separation, identification, and integration into the university lifestyle were coping strategies employed by the first-year students. Conclusion: Raising the consciousness of the university community (management, lecturers and non-teaching staff, and even older colleagues) to render necessary assistance, provide necessary support, and motivate first-year students to develop workable strategies that will help them cope with the university demands were recommended.